2017
DOI: 10.1016/j.deveng.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of medical devices to diagnose pre-eclampsia in low-resource settings

Abstract: Background Maternal mortality remains a major health challenge facing developing countries, with pre-eclampsia accounting for up to 17 percent of maternal deaths. Diagnosis requires skilled health providers and devices that are appropriate for low-resource settings. This study presents the first cost-effectiveness analysis of multiple medical devices used to diagnose pre-eclampsia in low- and middle-income countries (LMICs). Methods Blood pressure and proteinuria measurement devices, identified from compendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, in low‐ and middle‐income countries, multiple system‐level barriers exist that impact implementation, evaluation, and sustainability of such approaches. Economic analysis of basic screening devices such as blood pressure monitors and urine dipsticks for use in low‐resource settings has shown that simple devices are most cost‐effective . The more sophisticated tools for first‐trimester screening must be evaluated in this context.…”
Section: Resource‐based Approach To Screeningmentioning
confidence: 99%
“…However, in low‐ and middle‐income countries, multiple system‐level barriers exist that impact implementation, evaluation, and sustainability of such approaches. Economic analysis of basic screening devices such as blood pressure monitors and urine dipsticks for use in low‐resource settings has shown that simple devices are most cost‐effective . The more sophisticated tools for first‐trimester screening must be evaluated in this context.…”
Section: Resource‐based Approach To Screeningmentioning
confidence: 99%
“…In low-resource settings in LMICs, blood pressure is likely not measured during routine antenatal visits due to equipment cost and lack of trained personnel [ 85 ]. Researchers have created lower-cost blood pressure monitors for pregnancy, but few of them have been validated for pre-eclampsia diagnosis [ 86 , 87 ].…”
Section: Low-cost Technologies To Improve Access To Pre-eclampsia Scr...mentioning
confidence: 99%
“…Despite these leaps and bounds in medical technology and diagnostic methodologies, many barriers to standard clinical diagnosis remain, such as physician hesitance to adopt new diagnostic methodologies with small bodies of evidence, slow reimbursement from third-party payers for molecular diagnostic techniques, the need to promptly identify drug-resistant and novel pathogens, the need to diagnose culture-negative infections, the inability to promptly differentiate bacterial and viral respiratory infections, and the need for simple and easy to use testing methods when training technicians [ 24 , 26 , 27 , 59 , 60 ]. In addition to the roadblocks to standard clinical care, further limitations exist for the large variety of resource-limited settings such as low- and middle-income countries (LMICs), the Global South, rural areas, and disaster-stricken regions, including the lack of reliable infrastructure for communication, clean water, and power sources, the tendency for infectious diseases to spread rapidly due to crowding after a natural disaster, lack of access to expensive reagents and devices, lack of trained personnel for complex diagnostic techniques, and increased exposure to disease vectors like insects and livestock [ 25 , 61 , 62 , 63 , 64 ]. Biochemical methods like enzyme-linked immunosorbent assays (ELISA) and molecular diagnostic methods, particularly those utilizing nucleic acid tests (NATs) or nucleic acid amplification tests (NAATs) based on the polymerase chain reaction (PCR) and its many derivatives, have proven to be invaluable in overcoming these obstacles when diagnosing both infectious diseases and non-transmissible conditions in a clinical setting due to their relatively simple operation, quantitative results, molecular-level identification of biomarkers, high sensitivity, and relatively low cost in most cases [ 19 , 24 , 25 , 27 , 28 , 38 , 65 , 66 ].…”
Section: Medical Diagnosismentioning
confidence: 99%